Characterization of Tail Sheath Protein of N4-Like Phage phiAxp-3 - Zhang, Zheng; Tian, Changyu; Zhao, Jiangtao; Chen, Xiao; Wei, Xiao; Li, Huan; Lin, Weishi; Feng, Ruo; Jiang, Aimin; Yang, Wenhui; Yuan, Jing; Zhao, Xiangna (Frontiers in Microbiology, 2018)
Achromobacter phage phiAxp-3, an N4-like bacteriophage, specifically recognize A. xylosoxidans lipopolysaccharide (LPS) as its receptor. PhiAxp-3 tail sheath protein (TSP, ORF69) shares 54% amino acid sequence identity with the TSP of phage N4 (gp65); the latter functions as a receptor binding protein and interacts with the outer membrane receptor NfrA of its host bacterium. Thus, we hypothesized that ORF69 is the receptor-binding protein of phiAxp-3. In the present study, a series of ORF69 truncation variants was constructed to identify the part(s) of this protein essential for binding to A. xylosoxidans LPS. Phage adsorption and enzyme-linked immunosorbent assays showed that amino acids 795–1195 of the TSP, i.e. ORF69(795–1195), are sufficient and essential for receptor and binding. The optimum temperature and pH for the functions of ORF69 and ORF69(795–1195) are 4/25 oC and 7, respectively. In vitro cytotoxicity assays showed that ORF69 and ORF69(795–1195) were respectively toxic and nontoxic to a human immortalized normal hepatocyte cell line (LO2; doses: 0.375–12μg). The potential of this nontoxic truncated version of phiASP-3 TSP for clinical applications is discussed.